1995
DOI: 10.1002/hep.1840220317
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of lectin-reactive alpha-fetoprotein as an early indicator of hepatocellular carcinoma in the follow-up of cirrhotic patients

Abstract: Levels of two types of lectin-reactive alpha-fetoprotein (AFP), designated AFP-L3 and AFP-P4+P5, were analyzed with Lens culinaris agglutinin A and AFP-P4+P5 with erythroagglutinating phytohemagglutinin, respectively, in an attempt to determine the utility and significance of these macromolecules as early indicators of hepatocellular carcinoma during the periodic follow-up of cirrhotic patients. The subjects were 51 of 190 consecutive cirrhotic patients in whom hepatocellular carcinoma developed during a 6-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(88 citation statements)
references
References 24 publications
0
87
1
Order By: Relevance
“…Finally, 17 articles were included in our study (Fig. 1, Table 1) [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Eleven studies included data on more than one tumor marker [70, 71, 73-77, 79-81, 83], and 4 of them provided sensitivity and specificity of a combination of two tumor markers [70,74,77,79].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 17 articles were included in our study (Fig. 1, Table 1) [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Eleven studies included data on more than one tumor marker [70, 71, 73-77, 79-81, 83], and 4 of them provided sensitivity and specificity of a combination of two tumor markers [70,74,77,79].…”
Section: Resultsmentioning
confidence: 99%
“…AFP-L3 has been reported to be a useful marker in the early diagnosis of HCC. Its diagnostic accuracy varied from 17% to 42% in small HCC of Ͻ2 cm (22)(23)(24)(25). Previous work has suggested that simultaneous measurement of serum des-␥-carboxy prothrombin and AFP-L3 in patients with small HCC increased the sensitivity to 54.1%; specificity and accuracy increased to 97.8% and 84.1%, respectively (26).…”
Section: Discussionmentioning
confidence: 99%
“…AFP has been the core biomarker for HCC, but because of the low sensitivity of the biomarker guidelines of the American Association for the Study of Liver Diseases do not include the usage of the AFP test for HCC surveillance for high-risk patients (27). AFP-L 3 %, an LCA-retained fuco-fraction of AFP, has been suggested as a means to complement the unsatisfactory clinical outcomes that are particularly observed for HCC patients with low AFP serum level (28,29). However, studies failed to support the increased validity of AFP-L 3 % over the use of AFP alone.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates a limited utility of AFP because of low specificity for prediction or diagnosis of HCC. Because it has been reported that the ratio of AFP-L 3 to total AFP could be highly specific for HCC, AFP-L 3 has been a preferred HCC biomarker to AFP levels and extensive investigations culminated in FDA-approval of an AFP-L 3 lab test to determine the risk of developing liver cancer in patients with chronic liver disease (11). Besides AFP-L 3 , several glycan indicators of a relationship with cancer states including CA15-3 and CA19-9, have been reported in terms of relationship with cancer states (12,13).…”
mentioning
confidence: 99%